Problems of Sensing Mentality and Development of Basic Human Potential Inventory: [Permasalahan Sensing Mentality dan Penyusunan Instrumen Alat Ukur Potensi Dasar Manusia] - Riyono, Bagus; Intani, Zahra Frida (Faculty of Psychology, Universitas Surabaya, 2024)
This study aims to develop an inventory that represents the phenomenon of human behavior experiencing sensing mentality. Sensing mentality is a condition in which an individual experiences satisfaction and happiness only at the level of sensation or sensory experience, and these sensations are instantaneous and impulsive. The instrument is developed based on the theory of basic human potential, concluding that basic human potential possesses four layers or dimensions, namely: (1) sensing; (2) reasoning; (3) empathy; and (4) conscience (Riyono, 2023). Study subjects consisted of individuals aged 18-68 years (n = 207) to represent those active in society from various groups. Results from the confirmatory factor analysis (CFA) showed model fit indicators, with RMSEA = 0.087 and TLI = 0.840. An indication of a tendency for sensing mentality is when the score on the sensing dimension is dominant over the other dimensions. Studi ini bertujuan untuk menyusun alat ukur yang dapat merepresentasikan fenomena perilaku manusia yang kondisi jiwanya tengah mengalami sensing mentality. Sensing mentality adalah kondisi jiwa individu yang mengalami kepuasan dan kebahagiaan hanya pada tingkatan sensasi atau pengalaman indrawi, dan sensasi tersebut bersifat instan dan impulsif. Alat ukur disusun berdasarkan teori tentang potensi dasar manusia yang menyimpulkan bahwa potensi dasar manusia terdiri dari empat lapisan atau dimensi, yaitu: (1) sensing; (2) reasoning; (3) empathy; dan (4) conscience (Riyono, 2023). Subjek studi terdiri dari individu dengan rentang usia 18-68 tahun (n = 207), untuk merepresentasikan manusia aktif di masyarakat dari berbagai kelompok. Hasil dari confirmatory factor analysis (CFA) menunjukkan indikator model fit dengan RMSEA = 0,087 dan TLI = 0,840. Indikasi adanya kecenderungan sensing mentality adalah ketika skor dimensi sensing dominan dibandingkan dimensi lainnya.